2011
DOI: 10.1111/j.1365-2486.2011.02513.x
|View full text |Cite
|
Sign up to set email alerts
|

A welcome can of worms? Hypoxia mitigation by an invasive species

Abstract: Invasive species and bottom-water hypoxia both constitute major global threats to the diversity and integrity of marine ecosystems. These stressors may interact with unexpected consequences, as invasive species that require an initial environmental disturbance to become established can subsequently become important drivers of ecological change. There is recent evidence that improved bottom-water oxygen conditions in coastal areas of the northern Baltic Sea coincide with increased abundances of the invasive pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
154
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 159 publications
(165 citation statements)
references
References 82 publications
7
154
3
1
Order By: Relevance
“…m −2 should have a slight stimulatory effect on benthic P release, whereas at abundances above 3500 ind. m −2 P immobilisation would be greatly increased (Norkko et al 2012). , which we did not find (Fig.…”
Section: Low Influence On P Fluxescontrasting
confidence: 43%
See 1 more Smart Citation
“…m −2 should have a slight stimulatory effect on benthic P release, whereas at abundances above 3500 ind. m −2 P immobilisation would be greatly increased (Norkko et al 2012). , which we did not find (Fig.…”
Section: Low Influence On P Fluxescontrasting
confidence: 43%
“…3a). Thus, our experiment does not confirm the model result of Norkko et al (2012) but corroborates other experimental studies showing insignificant effects of bioturbation by Marenzelleria on benthic DIP exchange (Karlson et al 2005, Urban-Malinga et al 2013). …”
Section: Low Influence On P Fluxessupporting
confidence: 35%
“…We did not include indicators for non-native species in this study. However, there is a growing understanding that, contrary to the normally negative perception of the ecological impact of non-native species, some species may provide significant ecosystem services in specific cases (Norkko et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have attempted to investigate the connection between flocculation and the Fe distribution in boreal estuarine sediments. This is a significant gap in existing 10 knowledge, since an increasing number of studies have demonstrated the importance of reactive Fe minerals in sedimentary diagenesis in boreal coastal areas, including their roles in the anaerobic oxidation of methane (AOM) Egger et al, 2015a) and in phosphorus retention in sediments (Reed et al, 2011;Norkko et al, 2012;Egger et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%